2012
DOI: 10.1093/annonc/mdr062
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of mucinous histology for patients with radically resected stage II and III colon cancer

Abstract: For patients with stage II and III colon cancer who underwent curative surgery, mucinous histology has no significant correlation with prognosis compared with NMC. This retrospective analysis suggests a comparable benefit from adjuvant chemotherapy for MC compared with NMC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
88
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 27 publications
16
88
3
1
Order By: Relevance
“…Patients with the MA histotype had a worse disease-free survival than AD patients without neo-and adjuvant chemotherapy (86 vs. 161 months, P < 0.001; and 86 vs. 128 months, P < 0.001; respectively); however, when neo-and adjuvant chemotherapy were added, the differences in DFS between MA and AD were not of statistical significance. In agreement with our study [10], a recent analysis suggested that a comparable benefit was derived from adjuvant chemotherapy for both stage II and III MA and AD after radical resection. In contrast, a poor response to chemotherapy was previously demonstrated in MA patients who received palliative chemotherapeutic treatment [24,28,29].…”
Section: Discussionsupporting
confidence: 93%
“…Patients with the MA histotype had a worse disease-free survival than AD patients without neo-and adjuvant chemotherapy (86 vs. 161 months, P < 0.001; and 86 vs. 128 months, P < 0.001; respectively); however, when neo-and adjuvant chemotherapy were added, the differences in DFS between MA and AD were not of statistical significance. In agreement with our study [10], a recent analysis suggested that a comparable benefit was derived from adjuvant chemotherapy for both stage II and III MA and AD after radical resection. In contrast, a poor response to chemotherapy was previously demonstrated in MA patients who received palliative chemotherapeutic treatment [24,28,29].…”
Section: Discussionsupporting
confidence: 93%
“…There are 3759 English literatures in original search, after exclusion and screening, 28 English literatures (Cusack et al, 1996;Sun et al, 1996;Wu et al, 1996;Enriquez et al, 1998;Cerottini et al, 1999;Consorti et al, 2000;Nozoe et al, 2000;Kanemitsu et al, 2003;Chen et al, 2004;Du et al, 2004;Papadopoulos et al, 2004;Kang et al, 2005;You et al, 2006;Grillo-Ruggieri et al, 2007;Hill et al, 2007;Lee et al, 2007;Farhat et al, 2008;Pande et al, 2008;Catalano et al, 2009;Min et al, 2009;Song et al, 2009;Xie et al, 2009;Sultan et al, 2010;Catalano et al, 2011;Jivapaisarnpong et al, 2011;Hyngstrom et al, 2012;Langner et al, 2012;Yamaguchi et al, 2012) and 2 Chinese literatures (Songqing et al, 2002;Miao et al, 2005) meet the requirements. In the 30 literatures, 21 literatures can be used for Meta analysis of the relationship of mucinous adenocarcinoma and TNM staging, including 444489 cases, in which mucinous adenocarcinoma were 45050 cases, accounting for 10.1% of all cases; 21 literatures can be used for Meta analysis of relationship of mucinous adenocarcinoma and prognosis, including 450804 cases, in which mucinous adenocarcinoma were 45354 cases, accounting for 10.1% of all cases.…”
Section: The General Results Of Selected Literaturementioning
confidence: 99%
“…New perspectives are given by gene and protein research [2,22,27,28], evaluation of apoptosis-regulating proteins in the context of tumor progression and response to therapy [29], and analysis of molecular signatures in colorectal cancer [30,31].…”
Section: Discussionmentioning
confidence: 99%